Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1115/1.4039635
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Seismic Fragility Analysis of Unanchored Steel Storage Tanks Accounting for Uncertain Modeling Parameters

Abstract: Catastrophic failure of the above ground steel storage tanks was observed during past earthquakes, which caused serious economic and environmental consequences. Many of the existing tanks were designed in the past with outdated analysis methods and with underestimated seismic loads. Therefore, the evaluation of the seismic vulnerability of these tanks, especially ones located in seismic prone areas, is extremely important. Seismic fragility functions are useful tools to quantify the seismic vulnerability of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…Salzano et al (2003) or (2) analytical approaches covering single failure modes that use simplified or refined models for fluid-structure interaction modelling, e.g. Iervolino et al (2004), Buratti and Tavano (2014), , (2017), Cortes and Prinz (2017) and Phan et al (2019). Regarding analytical approaches, fragility functions are derived using the results of nonlinear dynamic analyses of structural models; therefore, the accuracy of fragility functions strongly depends on the reliability of relevant models.…”
Section: Background and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Salzano et al (2003) or (2) analytical approaches covering single failure modes that use simplified or refined models for fluid-structure interaction modelling, e.g. Iervolino et al (2004), Buratti and Tavano (2014), , (2017), Cortes and Prinz (2017) and Phan et al (2019). Regarding analytical approaches, fragility functions are derived using the results of nonlinear dynamic analyses of structural models; therefore, the accuracy of fragility functions strongly depends on the reliability of relevant models.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Generally, uncertain modelling parameters of storage tanks include both geometry and material properties. In this respect, in order to find which modelling parameters entail a significant effect on the seismic response of unanchored tanks, Phan et al (2019) carried out a screening study; the authors found that the liquid filling level, among other geometry and material random variables such as shell plate thickness, baseplate thickness, steel yielding strength and liquid density, is the most significant one for the purpose of determining fragility functions. They have also found that fragility curves developed considering only the most significant modelling parameter are almost the same as those considering all random variables.…”
Section: Kriging-based Lf Model With Random Effectsmentioning
confidence: 99%
“…This study aims to derive the seismic fragility of a steel tank containing liquids, which is an important facility of industrial complexes, considering the hydrodynamic forces caused by oscillating liquids. Steel tanks can be classified to two groups, anchored and unanchored tanks, and it has been reported that their dynamic behaviors are quite different [35,36]. This study examines the seismic fragility of an anchored steel liquid storage tank, which was relatively less well studied in previous studies but still an important facility of industrial complexes.…”
Section: Fe Model Of Steel Liquid Storage Tankmentioning
confidence: 99%
“…The uplift mechanism of the tanks can be simulated by a rotation spring that represents the rocking resistance of the base, as shown in Fig.7. The behaviour of the resistance spring can be obtained using either the simplified approach presented by Malhotra and Veletsos (1994) [8] or the more refined approach presented by Phan et al (2018) [9].…”
Section: Numerical Modelling Of Storage Tanksmentioning
confidence: 99%